Analysis of BAZNAS Tangerang District Performance - Rahma Suryaningtyas (Center of Strategic Studies (PUSKAS) BAZNAS, 2018)
Zakat has a significant role in the field of economics, as well as having social and moral implications and alleviating poverty. There is a huge gap, however, between targeted zakat collection, which reached Rp 20 billion, and actual zakat collection, which equals Rp 2 billion in 2017. This research was carried outin order to evaluate the performance of BAZNAS Tangerang District. The purposive sampling technique wasused in this research. The analytical method used wasthe National Zakat Index(NZI) with a method of calculation known as the Multi-Stage Weighted Index, which measured zakat performance based on macro and micro dimensions. The results of the assessment of the NZI of Tangerang Districtis 0.60 that showed a fairly good condition based on classification of zakat performance. This research provides recommends for BAZNAS Tangerang District to improve its performance. Keywords: BAZNAS Performance, NZI, Tangerang District, Zakat